Essays on extension education and farmers' adoption of oilseeds crops and conservation practices - Andrango Quimbiulco, Graciela Cristina (Kansas State University, 2016)
Adoption of technological improvements are crucial to increase agricultural productiviy to help reduce poverty by obtaining higher farm incomes due to higher productivity and lower production costs. However, the introduction of new agricultural technologies has not always been successful or had diffuse adoption. Factors that determine farmers’ adoption decisions are: 1) farm and farmers' characteristics; 2) technology attributes, and 3) the farming objective. Understanding these factors and how they affect adoption of new technologies on the farm is crucial to assure higher levels of adoption. The over all purpose of this thesis is to explore the adoption process of new technologies and practices by farmers. This is accomplished through three essays to meet the objectives of the thesis. The purpose of the first essay was to evaluate whether or not farmers in the western U.S. are willing to grow specialized oilseed crops that could be used for certified hydrotreated renewable jet (HRJ) fuel production and incorporate them into existing wheat-based production systems under contract. Results indicate that providing oilseeds crops and contracts with desired attributes and features would positively affect farmers' decisions to incorporate oilseed crops into their rotation system. Preferred seed and contract attributes that may affect a farmer’ adoption decision differ across different geographic regions of the U.S. The second essay focused on identifying factors that impact participation and farmers' decision to adopt soil conservation and fertilization management practices for cassava producers in Thailand and Vietnam. Results indicate that asset ownership and cassava yield positively influence participation. Adoption of new practices was positively linked to farmers’ participation in training activities, use of fish ponds (as a measure of alternative agricultural practices), presence of a nearby starch factory, and slope of the land. Finally, the purpose of the third essay was to examine extension educators' characteristics that affect educators' selection decision of outreach methods in the U.S. This essay examines the diffusion process that impacts adoption of best management practices by farmers. The decision extension educators make for selecting a teaching method is affected by the relationship between the objectives of the learning process and the characteristics of the teaching method.
Keywords: Adoption; Extension; Latent Class Model; Participatory Methodologies